Recitation of the Qur’an in the Batunggu kubur (Tradition for the Astambul Community) - Muzdalifah, Muzdalifah; M. Fahmi al-Amruzi; Anida Yuspa; Anwar Hafidzi (Indonesian Journal of Islamic Jurisprudence, Economic and Legal Theory, 2024)
Abstract This research raises a tradition, namely the recitation of Qur'an in Batunggu kubur which is done after the burial of the dead. In this Batunggu kubur the Qur'an is read in groups from the the beginning to the end until the specified time. The purpose of this research is to find out how the meaning of the community and the procedure for the implementation of the implementation of the Astambul Subdistrict community towards the reading of the Qur'an in Batunggu kubur. Type of The type of research used is qualitative research using descriptive-analytical studies. The result of this research is that Batunggu kubur is permissible because it has a positive and beneficial meaning, both for the people of Astambul Sub-district. Positive and beneficial meaning, both for people who read the Qur'an on the grave and for the deceased. Over the grave as well as for the deceased and the living and does not violate the rules of shara'. Regarding the procedure for its implementation, the recitation of the Qur'an in the Batunggu kubur tradition there are three variations. First, every person who Batunggu kubur gets a share of each juz to be completed. Second, the person who Batunggu kubur has no obligation to complete the reading, and there are no strict rules regarding the recitation of the the Qur'an. Third, everyone who Batunggu kubur has an obligation to complete the Qur'an. Keywords: Qur’an Reading, Tradition, Batunggu kubur Abstrak Penelitian ini mengangkat sebuah tradisi, yaitu pembacaan Al Qur'an dalam Batunggu kubur yang dilakukan setelah penguburan jenazah. Dalam Batunggu kubur ini Al Qur'an dibaca secara beramai-ramai dari awal sampai akhir sampai waktu yang telah ditentukan. Tujuan dari penelitian ini adalah untuk mengetahui bagaimana pemaknaan masyarakat dan tata cara pelaksanaan masyarakat Kecamatan Astambul terhadap pembacaan Al-Qur'an dalam Batunggu kubur. Jenis penelitian yang digunakan adalah penelitian kualitatif dengan menggunakan studi deskriptif analitis. Hasil dari penelitian ini adalah Batunggu kubur diperbolehkan karena memiliki makna yang positif dan bermanfaat, baik bagi masyarakat Kecamatan Astambul. Makna positif dan bermanfaat, baik bagi orang yang membaca Al-Qur'an di atas kubur maupun bagi orang yang meninggal. Di atas kubur maupun bagi orang yang meninggal dan yang masih hidup serta tidak melanggar aturan syara'. Mengenai tata cara pelaksanaannya, pembacaan al-Qur'an dalam tradisi Batunggu kubur terdapat tiga variasi. Pertama, setiap orang yang Batunggu kubur mendapat bagian masing-masing satu juz untuk dikhatamkan. Kedua, orang yang melakukan Batunggu kubur tidak memiliki kewajiban untuk menuntaskan bacaannya, dan tidak ada aturan yang ketat mengenai bacaan Al-Qur'an. Ketiga, setiap orang yang melakukan Batunggu kubur memiliki kewajiban untuk mengkhatamkan Al Qur'an. Kata kunci: Pembacaan Al-Qur'an, Tradisi, Batunggu kubur